Crystal structure of 2-hydroxyethyl-triphenylphosphonium tetracyanidoborate, C24H20BN4OP - Topp Anke; Konstantin Lukas; Köckerling Martin (Zeitschrift für Kristallographie - New Crystal Structures)
C24H20BN4OP, monoclinic, P21/n (no. 14), a = 14.1418(2) Å, b = 10.5821(1) Å, c = 15.4684(2) Å, β = 94.622(1)°, V = 2307.32(5) Å3, Z = 4, Rgt(F) = 0.0203, wRref = 0.0408, T = 293(2) K.